ARTERIAL HYPERTENSION IN A VERY OLD: SIGNIFICANCE OF THE BIOLOGICAL AGE - Yu. V. Kotovskaya; О. N. Tkacheva; N. К. Rukikhina; V. S. Ostapenko (Кардиоваскулярная терапия и профилактика, 2017)
Elderly population is heterogenic, and persons with the same chronological age differ greatly by their physical and cognitive functioning. Regardless the convincing witness on the adverse influence of raised blood pressure (BP) in a middle age persons, its influence on the prognosis of a very old is still debatable, as the question, whether to treat arterial hypertension (AH) in elderly, and if so, how intensively. The article focuses on the results of observational and randomized clinical studies that make it to decide that not  the  chronological,  but  biological age  is an  important  criteria  for decision on AH management in elderly. The article presents in details mechanisms  interacting in BP regulation, and influence of BP on the risk of morbidity and mortality in elderly. Also, the current guidelines are cited, on antihypertension treatment, as the issues dicussed on AH treatment in elderly, that require further investigation.